Assessment of Accuracy of COSMIC and KOMPSAT Radio Occultation Temperature and Pressure - Descalzo Karl Philippe A.; Macalalad Ernest P. (E3S Web of Conferences)
Radio Occultation is a technique used by orbiting satellites to measure planetary atmosphere properties like temperature, pressure, and water vapor. The aim of this study is to assess the radio occultation temperature and pressure profiles from the Constellation Observing System for Meteorology, Ionosphere and Climate 2 (COSMIC-2) and Korean Multi-purpose Satellite 5 (KOMPSAT5) using data from collocated radiosonde stations over the Philippines. Their deviations are analyzed using their mean and standard deviations. COSMIC-2 and KOMPSAT-5 temperature and pressure have good agreement with radiosondes in the stratosphere. From January to April of 2020, COSMIC-2 temperature standard deviation peaks with 0.072 K at 24.6 km. COSMIC-2 and KOMPSAT-5 pressure generally decreases with altitude. COSMIC-2 pressure standard deviation peaks with 0.06 hPa at 15 km. KOMPSAT-5 temperature standard deviation gradually increases with altitude with observed deviation peaks with 0.6 K at ~26.5 km. KOMPSAT-5 pressure standard deviation peaks with 0.02 hPa at 15 km. Seasonal variations between KOMPSAT-5 and radiosonde are usually lower in pressure deviation compared to temperature deviation. KOMPSAT-5 temperature standard deviation peaks at 23.24 km with 0.07 K during summer. KOMPSAT-5 pressure deviation is generally larger in the autumn season with a value of ~>0.02 hPa at 15 km. The quality of these results shows potential in COSMIC and KOMPSAT as high-quality applications for weather prediction.